2014
DOI: 10.5455/medscience.2014.03.8126
|View full text |Cite
|
Sign up to set email alerts
|

Death Caused by Honey Bee Stings: Case Report

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
4
0
1
Order By: Relevance
“…In the present study about 7.9 LD 50 of antivenom is required in children of 10 kg. The calculated LT 50 of 2.10 and 3.72 hr for child and adult human respectively, agree with the report indicating that honeybee venom from over 50 stings can kill within short period of time [86]. The fact that 200 stings could cause envenoming syndrome in adult with type 2 diabetes and prostate cancer [87] and non-diseased human [83] shows the newly derived formula may be used for determination of effective dose of honeybee antivenin for all the population segments.…”
Section: Treatment Of Apitoxicosissupporting
confidence: 85%
“…In the present study about 7.9 LD 50 of antivenom is required in children of 10 kg. The calculated LT 50 of 2.10 and 3.72 hr for child and adult human respectively, agree with the report indicating that honeybee venom from over 50 stings can kill within short period of time [86]. The fact that 200 stings could cause envenoming syndrome in adult with type 2 diabetes and prostate cancer [87] and non-diseased human [83] shows the newly derived formula may be used for determination of effective dose of honeybee antivenin for all the population segments.…”
Section: Treatment Of Apitoxicosissupporting
confidence: 85%
“…The inflammation due to bee stings is related to number of stings and individual's sensitivity [30]. Sudden deaths were reported due to bee stings in studies in Turkey [31]. A study has shown that just 36% of parents possess the knowledge that the stinger should be pulled out as soon as possible [32].…”
Section: Discussionmentioning
confidence: 99%
“…It depends on various factors like location and number of stings, history of previous allergic reactions, pre-existing coronary atherosclerosis. 5,9 We report a case of death due to Anaphylactic Shock consequent upon multiple bee sting envenomation.…”
Section: Introductionmentioning
confidence: 99%
“…After the sting, honeybee dies as part of its digestive tract, venom sac and stinger are eviscerated and left behind. 5 Anaphylaxis is a medical emergency and a life-threatening acute hypersensitivity reaction. It is defined as a rapidly evolving, generalized, multi-system, allergic reaction which may prove fatal in absence of proper treatment due to respiratory collapse.…”
Section: Introductionmentioning
confidence: 99%